Ventral stabilization of thoracic kyphosis through bilateral intercostal thoracotomies using SOP (String of Pearls) plates contoured after a 3‐dimensional print of the spine. Issue 6 (9th August 2018) - Mathiesen, Christina B.; de la Puerta, Benito; Groth, Anna M.; Rutherford, Scott; Cappello, Rodolfo
Abstract: Objective: To describe a novel vertebral body stabilization and report its outcome in dogs with thoracic kyphosis and secondary myelopathy. Study design: Case series. Animals: Six pugs with thoracic kyphosis and secondary myelopathy. Methods: Medical records (2012‐2017) of dogs with chronic progressive pelvic limb ataxia and ambulatory proprioceptive paraparesis due to thoracic kyphosis were reviewed. Dogs were evaluated via MRI and computed tomography. A 3‐dimensional print of the kyphotic vertebral segment was used to precontour the SOP (String of Pearls) plates. Bilateral double, dorsal intercostal thoracotomies were performed to place precontoured SOP on the vertebral bodies. Long‐term (6‐16 months) clinical outcome was determined on the basis of neurological scoring (NS) and owner questionnaire. Results: The only intraoperative complication consisted of a lung laceration due to preexisting adhesions. Postoperative complications included seroma formation (n = 2) and incidental radiographic evidence of screw breakage (n = 2). NS at presentation ranged between 2 and 4 and improved to 1 at long‐term follow‐up in all dogs but 1 (NS = 2). All owners felt that their dog had excellent quality of life at follow‐up. Conclusion: In spite of the challenging local anatomy, all dogs undergoing vertebral stabilization with SOP placement experienced a good clinical outcome. Clinical significance: Stabilization of vertebral bodies with precontoured SOP placed through bilateral thoracotomies may be considered as a treatment option for dogs with thoracic kyphosis and secondary myelopathy.